2010
DOI: 10.1111/j.1749-6632.2010.05802.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal hormones and the regulation of β‐cell mass

Abstract: Type 2 diabetes occurs due to a relative deficit in β-cell mass or function. Glucagon-like peptide 1 (GLP-1), glucosedependent insulinotropic polypeptide (GIP), cholecystokinin (CCK), and gastrin are gastrointestinal hormones that are secreted in response to nutrient intake, regulating digestion, insulin secretion, satiety, and β-cell mass. In this review, we focus upon β-cell mass regulation. β-cell mass expands through β-cell proliferation and islet neogenesis; β-cell mass is lost via apoptosis. GLP-1 and GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 125 publications
(280 reference statements)
2
46
0
Order By: Relevance
“…In recent years, however, several lines of evidence have emerged to suggest that there is much more to the biology of gastrin than is indicated by earlier work 25, 35. Gastrin has been shown to display proliferative,36, 37 antiapoptotic,38 and cell migration39 properties. In previous reports, the concentration of gastrin in serum was found to be significantly increased during myocardial infarction 13.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, however, several lines of evidence have emerged to suggest that there is much more to the biology of gastrin than is indicated by earlier work 25, 35. Gastrin has been shown to display proliferative,36, 37 antiapoptotic,38 and cell migration39 properties. In previous reports, the concentration of gastrin in serum was found to be significantly increased during myocardial infarction 13.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism(s) adopted by GLP-1 and GIP to modulate cell proliferation and function implicates multiple signalling pathways. The pathways characterised include those acting via the G-protein-coupled receptors that lead to activation of cAMP, protein kinase A (PKA) and the cAMP response element-binding protein (CREB) cascade to directly regulate genes involved in proliferation and apoptosis, and other pathways determining phosphorylation of Akt and mitogen-activated protein kinases [108]. The ghrelin genederived peptides and exendin-4 exert cyto-protective effects in human pancreatic islet endothelial cells.…”
Section: Contributors To Maintenance Of Islet Cell Mass In Adult Rodentsmentioning
confidence: 99%
“…b-cells (18). Increased expression of islet GLP-1 receptor after RYGB as reported by Lindqvist et al could contribute to increased b-cell mass.…”
mentioning
confidence: 86%
“…Since then, several animal and human investigations have shown that RYGB and other procedures can improve T2D through a variety of GI mechanisms, including changes in gut hormones (18,19,21), bile acids metabolism (28), intestinal microbiota, nutrient sensing (29), and reprogramming of intestinal glucose metabolism (30). This demonstrates a critical and previously underappreciated role of the gut in glucose metabolism and underscores the importance of further research on the mechanisms of action of GI surgery.…”
mentioning
confidence: 99%